Salivary α-amylase activity and flow rate explain differences in temporal flavor perception in a chewing gum matrix comprising starch-limonene inclusion complexes. (August 2022) - Goza, Jennifer L.; Ziegler, Gregory R.; Wee, Josephine; Hayes, John E.; Hopfer, Helene
Graphical abstract: Highlights: Temporal Check-All-That-Apply (TCATA) shows flavor differences in chewing gums with and without starch-guest ICs. Flavor from inclusion complex (IC) gums differs in individuals due to saliva composition. Flavor perception differs between individuals due to differences in salivary α -amylase activity (sAA) and salivary flow rate (sFR) Flavor perception of ICs is dependent on freeing of aroma by sAA and dilution by sFR. Abstract: Starch-guest inclusion complexes (ICs) are a novel, clean-label flavor encapsulation system with the potential to improve stability of aroma volatiles. While amylase has been shown to modulate guest release in vitro, release by sensory perception has not been evaluated. Here, Temporal Check-All-That-Apply (TCATA) and CATA were used to compare flavor perception of starch-limonene ICs to uncomplexed limonene, and the differences in perception were explored as a function of participant salivary α-amylase activity (sAA) and salivary flow rate (sFR). High sFR levels decreased limonene perception while high sAA increased limonene perception, highlighting the potential influence of these physiological factors on flavor perception of foods. Temporal flavor perception of a chewing gum containing starch-limonene ICs and a second chewing gum containing uncomplexed limonene and corn starch (CTL) was evaluated by 99 untrained consumers who assessed taste, texture, and aroma attributes over 17 min by TCATA and CATA. In addition, participants were segmented into three clusters based on their sAA and sFR, and cluster TCATA curves for each sample and attribute were statistically compared. Overall, participants rated Citrus, Sour and Bitter ( p  < 0.05) significantly higher for the IC sample and rated Sweet higher for the CTL . For Citrus, Sour, and Bitter, s ignificant differences were observed between the three clusters for the IC chewing gum, while the CTL gum showed no significant differences for these three attributes. We demonstrate that flavor perception of starch-guest ICs varies with participants' salivary α-amylase activity and flow rate. Additionally, TCATA and CATA were found to be well suited to characterize flavor release systems over a long period of time as multiple flavor percepts can be simultaneously tracked.